Evaluating Organizational Performance Using SmartPLS: A Management Perspective - Moscato, Jason (APTISI Transactions on Management (ATM), 2023)
In the face of complex challenges in the global business environment, organizational performance is a major concern. Evaluation of organizational performance plays an important role in modern management. This research integrates the management perspective with a Structural Equation Modeling (SEM) approach using SmartPLS. Through keywords such as leadership, organizational culture, employee motivation, and other variables, this study identifies key factors that affect organizational performance. The results provide an in-depth view of how organizational management can influence and improve their performance. This research has significant practical implications for different types of organizations. This article details the methodology, variables, data analysis, and expected findings, all in the context of combining management and SEM for organizational performance evaluation.